Respuesta :

For this case we have the following polynomial:

 [tex] f (x) = 3x ^ 3 - 12x ^ 2 - 4x - 55 [/tex]

The first thing we must do is factor the polynomial.

We have then:

[tex] f (x) = (x-5) (3x ^ 2 + 3x + 11) [/tex]

Therefore, we observe that the common factor factor of the polynomial is:

[tex] (x-5) [/tex]

Answer:

The common factor factor of the given function is:

[tex] (x-5) [/tex]

Answer:

[tex](x-5)[/tex]


Step-by-step explanation:

The Factor Theorem tells us that substituting [tex]x=a[/tex]  into a polynomial  [tex]p(x)[/tex]  when divided by a linear factor  [tex](x-a)[/tex] will give us a value of 0 IF  [tex](x-a)[/tex] is a factor of the polynomial [tex]p(x)[/tex]

So, checking each of the 4 binomials, and getting a 0 as answer will tell us which one is a factor of the function given.


Putting [tex]x=-1[/tex]  for [tex](x+1)[/tex] into the function:

[tex]3(-1)^{3}-12(-1)^2-4(-1)-55\\=-66[/tex]

NOT a factor.


Putting [tex]x=-4[/tex]  for [tex](x+4)[/tex] into the function:

[tex]3(-4)^{3}-12(-4)^2-4(-4)-55\\=-423[/tex]

NOT a factor.


Putting [tex]x=5[/tex]  for [tex](x-5)[/tex] into the function:

[tex]3(5)^{3}-12(5)^2-4(5)-55\\=0[/tex]

IS a factor.


Putting [tex]x=2[/tex]  for [tex](x-2)[/tex] into the function:

[tex]3(2)^{3}-12(2)^2-4(2)-55\\=-87[/tex]

NOT a factor.


So we can see that only  [tex](x-5)[/tex]  is a factor.